1992
DOI: 10.1080/02640419208729915
|View full text |Cite
|
Sign up to set email alerts
|

Physical, physiological and performance differences between canadian national team and universiade volleyball players

Abstract: Volleyball has been described as an 'interval' sport with both anaerobic and aerobic components. At the higher skill levels, technical performance may be limited by physical characteristics as well as physical fitness, and performance characteristics such as speed and vertical jump. This investigation compared teams at the two uppermost levels of men's volleyball in Canada for differences in physical, physiological and performance characteristics. The subjects were members of the national (n = 15) and universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
1
22

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(123 citation statements)
references
References 8 publications
7
93
1
22
Order By: Relevance
“…Smith et al (26) suggested that technical performance may be limited by physical fitness, and performance characteristics such as speed and vertical jump. In order to enhance performance characteristics, plyometric training has been recommended to be integrated in the training program for athletes, because of the effect of longterm training on muscle-activation strategies and performance (27).…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al (26) suggested that technical performance may be limited by physical fitness, and performance characteristics such as speed and vertical jump. In order to enhance performance characteristics, plyometric training has been recommended to be integrated in the training program for athletes, because of the effect of longterm training on muscle-activation strategies and performance (27).…”
Section: Discussionmentioning
confidence: 99%
“…É importante considerar que, o componente estatura e envergadura do atleta juntos contribuem consideravelmente com a altura do alcance do salto vertical (5,19).…”
Section: Discussionunclassified
“…Volleyball is one of the most popular and commonly played team sport [1,2] with complex athletic, technical and tactical demands involving short and intensive physical efforts, such as jumps or powerful movements, during training and competi-tion [3][4][5][6][7][8]. Modern volleyball is very quick, and in recent years sport scientists have begun to concentrate their studies on such game-related events defined to be "keys" to success or "performance indicators" by statisticians and researchers [9,10].…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%